Bridging the Restitution Gap: Reforming Juvenile Justice for Child Homicide Cases - Herman, KMS; Tjhia, Kimico Margaretha (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2025)
The Indonesian juvenile justice system urgently needs reform to address a critical legal void: restitution for victims in child homicide cases. Current regulations lack specific provisions, creating uncertainty and hindering justice for both victims and young offenders. This research, employing a normative approach, analyzes how a transformed system can balance child rights protection, victim justice, and legal certainty. Drawing on principles of justice, utility, and legal certainty, it advocates for integrating restorative justice to facilitate restitution. The study reveals that restorative justice effectively allows restitution to function as both victim compensation and a crucial element in offender rehabilitation. This transformation is vital for the juvenile criminal justice system to fulfill its legal objectives and promote social justice.